Challenges and successes for the grantees and the Technical Advisory Group of WHO's influenza vaccine technology transfer initiative. Issue 45 (26th October 2016) - Grohmann, Gary; Francis, Donald P.; Sokhey, Jaspal; Robertson, James
Abstract: One of the aims of the WHO Global Action Plan for Influenza Vaccines (GAP) was to transfer influenza vaccine production technology to interested manufacturers and governments in developing countries, to enable greater influenza vaccine manufacturing capacity against any pandemic threat or pandemic. For this objective, the GAP was supported by an independent Technical Advisory Group (TAG) to assist WHO to select vaccine manufacturing proposals for funding and to provide programmatic support for successful grantees. While there were many challenges, for both the TAG and grantees, there were also notable successes with an additional capacity of 338–600 million pandemic vaccine doses being made possible by the programme between 2007 and 2015, and a potential capacity of more than 600 million by 2016/17 with up to one billion doses expected by 2018/19. Seasonal vaccine production was also developed in 4 countries with another 4–5 countries expected to be producing seasonal vaccine by 2018/19. The relatively small WHO investments – in time and funding – made in these companies to develop their own influenza vaccine production facilities have had quite dramatic results.